Pembangunan Kampung Tangguh Berbasis ke-RT-an di Desa Sukasari Kabupaten Cianjur - Rizki Hegia Sampurna (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
A resilient village is an integral part of Indonesia's national resilience concept and paradigm. Theoretically, resilient towns have a root in the idea of human security, particularly community security. The resilient town can be measured by readiness, social trust, leadership, collective efficacy, and place attachment. This program is carried out in RT 03 RW 13 Desa Sukasari Kec. Cilaku Kab. Cianjur. The program is planned within three implementation phases, three years. Because it is oriented towards social engineering, the methods used are lectures, FGD, control and monitoring, and gap analysis. Five priority programs in 2020-2021 have been determined in the initial phase, namely: education, religion, security and health, economic productivity, and environment. Meanwhile, the stakeholders of each program are RT management, DKM and asatidz, foundations and teachers, and cooperatives. These programs are integrated, both between programs and among stakeholders, with a community networking system. As a result, most targeted programs can be implemented well by the second half of their first year. Such as Madrasah Diniya, Al-Badar Foundation, majlis taklim, urban farming, development of public facilities, etc. The main challenge for this program is to maintain consistency in the performance of stakeholders to keep the program sustainable